Adsorption Free Energy of Biphenyl and Aniline on the Surface of Graphene at Different Temperatures - Kaphle, G. C.; Bhatta, B. P.; Bhatta, K.R.; Bhujel, P; Acharya, D.P.; Khadka, P.; KC, M. (Pragya Darshan प्रज्ञा दर्शन, 2025)
Adsorption free energy is important for the fundamental and practical aspect to describe the nature of the reaction and to understand the interconnection of the various ingredients involved in the adsorption process. It is also useful to understand the thermodynamics of the molecules in drug delivery, removal of contaminant and protein folding among other. Here, we used TIP3P water model as a solvent to find out the adsorption free energy of the biphenyl and aniline on the surface of graphene at different temperatures through NAMD (Nanoscale Molecular Dynamics) for simulations and VMD (Visual Molecular Dynamics) for molecular visualization and modeling of the system. Overall calculations is performed within the framework of Adaptive Biasing Force (ABF) method in different temperatures at 1.03×105 Pascal pressure. The value of adsorption free energy of the systems in the NPT ensembles increase as increasing the temperature on both the systems. The calculation reveals that at the surface of graphene, biphenyl has a higher adsorption free energy than aniline. The present calculation for biphenyl is in excellent agreement with the prior result at 300 K.